(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
The advanced sports level reached by many countries is the direction of progress witnessed by the world in various scientific fields, which was clear in achieving sports achievements, Most countries used the best methods and training tools in the field of sports in order to bring the player to a high level in the performance of basic skills for any game, and since the goal of any coach in guiding efforts to achieve achievement was to use specialized training and focus on the requirements of technical performance In the type of sports effectiveness, privacy in training is one of the basic laws governing the training process in achieving its goal, which is the high level of achievement and the use of modern educational means in the educational process is effective in reaching better learning with an economy of effort, time and money, especially when using appropriate educational means and the type of skill in terms of its type and characteristics, and that the level of performance in tennis in recent years has increased clearly and efforts have doubled The change to the high skill level and speed of performance significantly in the world as tennis is a sport that depends heavily on the factor of speed and type in performance methods and that the skills of ground tennis are difficult and complex as well as for many types